Syntactic Adjectival Grading in English Grammar Via New Media: A Study of Students in Imo State University - Ifeyinwa Juliana Umeh; Chioma Winner Onyeama (MultiTech Publisher, 2025)
Despite the significant roles syntactic Adjectival Grading plays in both spoken and written English, it still poses a problem to the users of English Language. This study aims at explaining how the use of new media will facilitate and enhance teaching and learning of syntactic grading using Chomsky’s, (1967) Transformational Generative Grammar Theory and Bergmann and Sams (2007) flipped classroom model. This study guided by two research questions, sampled 100 students from 3 departments in Imo state University, Owerri, using structured questionnaire. The results of the data were analyzed using simple percentages. The findings reveal that the students were not conversant with the use of adjectival grading. The researchers recommend that the teachers of English language should pay great attention to the teaching of the nuances of grammar, especially with regard to adjectival grading as this would enhance students’ competence